Pemodelan Matematika Karakteristik Pengeringan Lada Putih Pada Pengering Spouted Bed Dengan Perlakuan Preheating Gelombang Mikro - Andi Muhammad Akram Mukhlis; Nurul Fadhilah (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
To study the effect of drying on white pepper seeds, a thorough knowledge of the drying kinetics is required. The drying kinetics of a material can be explained using a mathematical model which is usually used to estimate the drying time of the material. This study aims to determine the appropriate drying mathematical model for drying white pepper spouted beds with microwave preheating treatment. The equipment used in this study was a spouted bed dryer designed for laboratory scale. The material used in this study was wet white pepper seeds obtained from smallholder plantations in Enrekang district, South Sulawesi province with an age of approximately 8-9 months after flowering. The white pepper was directly put into the spouted bed drying room for non-preheating treatment, while for the preheating treatment the pepper was stored in a container then put in a microwave oven for 2 minutes. During the drying process, several parameters for drying analysis are measured. There are seven different mathematical drying models evaluated. In determining the most appropriate mathematical model, model validation is required through statistical methods. The statistical methods used were correlation analysis, reduced chi-square (χ2) test, and root means square error (RMSE) analysis. Based on the analysis, the Weibull model fulfills the criteria to be the best model with the correlation coefficient r (0.99990) being the highest and the χ2 (0.00001) and RMSE (0.00385) values ​​being the lowest. Thus, the Weibull model can be used to predict drying time and moisture content.